Image Transmission in Hierarchically Modulated Signals over Fading and Shadowing Channels - Rahmat, Majid (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2013)
In order to have a higher throughput, it is essential to apply a higher order M-ary QAM modulation to yield more data on each carrier. This can be considered as the basis for adaptive transmission rate control where more parameters and signal information are available. In this thesis, M-ary modulation techniques are simulated over AWGN channel, Rayleigh fading channel and Log-Normal shadowing channel. To achieve the purpose of achieving higher throughput, it is necessary to recognize the performance indicators and investigate the criteria which are used for good performance. The five scenarios presented in this thesis are as follows: 1) Comparing the effect of Log-Normal Shadowing on different Hierarchical Modulations such as (64-QAM, 16-QAM, 4-QAM and 2-QAM). 2) The evaluation of BER of QAM system over AWGN and Rayleigh fading channels and considering the effect of shadowing. 3) Determine the important factors on the lognormal shadowing phenomena and how the factors affect this process. 4) Studying the relationship between the BER and variance in shadowing and fading channel. 5) The random input has been replaced by an image to investigate the effect of shadowing on quality of image. It is found that depth of shadowing influences the received signal quality and causes to have poor performance and throughput. Depth of shadowing is varied by the mean and variance of shadowing distribution function. Therefore, the Bit Error Rate (BER) of the system has been analyzed from low to high Eb/No through MATLAB/R2012a Simulink application in order to find out the effective factors on depth of fading phenomenon. It is observed that the system desirably works at high Eb/No. One of the significant parts of this research consists of the effects of Log-Normal Shadowing phenomenon on systems BER performance. Based on the results of the simulation, it is obvious that shadowing has a negative effect on the systems BER performance. In this study, 2-QAM system has received more attention because of having less sensitivity to shadowing phenomenon in comparison with 4, 16 and 64-QAM. Then the effective factors of shadowing have been studied and the results show that variance of Log-Normal distribution can be controlled as the only factor to control shadowing. This effect can be easily seen in the images, obtained. Keywords: Hierarchical Modulation, QAM Modulation, Multipath Fading Channel, AWGN Channel, Rayleigh Fading, Depth of Shadowing, Log-normal Shadowing ,Small Scale Fading and Large Scale Fading.

ÖZ: Alınan sinyal kalitesinin bağımsız kanal bozuklukları tarafından etkilendiği oldukça açıktır. Bu nedenle, kanalın farklı zaman örneklerinde alınan sinyal kalitesi üzerinde farklı bir rol oynayan yük belirleyeni bulmak için çeşitli faktörler vardır. Kanal bozuklukları daha az etkilenen faktörlere bağlı olarak, sistemdeki kaynak için bir artan fazlalık tanıtılacaktır. Bu teknik, alınan sinyal kalitesini artırmak amacıyla alıcılar için bir fırsat yaratmaktadır. Daha yüksek bir verim elde etmek için, yüksek mertebeli bir M-ary QAM modülasyonu uygulamak gereklidir. Bu nedenle, her bir alt taşıyıcı üzerinde, çok sayıda veri bulunacaktır. Bu konuyu adaptif iletim hızı kontrolü için bir temel olarak düşünebiliriz ki daha fazla parametre ve sinyal bilgisi değiştirmek için mevcut olacaktır. Bu tezde, çok yollu sönümleme, AWGN kanalı, Rayleigh kanalı ve Log-Normal dağılımı üzerinde benzetimleme edilir. Bu çalışmada, daha yüksek verime ulaşmak için, performans faktörleri tanımak ve performansın ne kadar iyi olduğu karar vermek için kullanılan kriterleri araştırmak gereklidir. Bu tezde sunulan Beş senaryo şunlardır: 1) farklı hiyerarşik Modülasyonlar (64-QAM, 16-QAM, 4-QAM ve 2-QAM) üzerinde Log on-Normal Gölgelemenin etkisini karşılaştırılması. 2) gölgeleme etkisi dikkate alınarak AWGN ve Rayleigh sönümlü kanallar üzerinden QAM sisteminin değerlendirilmesi. 3) Lognormal gölgeleme olayları üzerinde önemli fakförler ve nasıl bu süreci etkilemekleri belirlemek. 4) Faktörler sistemde nasıl kontrol edilebilir.5) Çıktıyı yapmak için, Rastgele giriş bir görüntü ile değiştirilmiştir. Bu alınan sinyal kalitesi ve zayıf performans ve kötü verim elde edilme nedenleri üzerinde solmaya etkiler derinliği olduğu bulunmuştur. Solma derinliği dağılım fonksiyonu sinyalin ortalama ve varyans ile değişir. Yani, sistemin Bit Hata Oranı (BER) solma fenomeni derinliği üzerine etkili olan faktörler bulmak için düşük MATLAB/R2012a Simülasyon uygulaması ile yüksek Eb / No analiz edilmiştir. Eb / No değeri artırarak, sistemin iyice çalıştığı görülmektedir. Bu araştırmanın önemli bölümlerinden biri, log-normal gölgeleme fenomen etkisidir. Simülasyon sonuçlarına göre, gölgeleme sistemlerinin system üzerinde olumsuz bir etkiye sahip olduğu açıkça ortadadır. Bu çalışmada, 2-QAM sistemi için diğerleri ile karşılaştırıldığında, fenomen gölgeleme içinde daha az hassasiyet olduğundan dolayı daha fazla ilgi çekiyor. Bu tezin ileri bölümlerinde, gölgeleme etkili faktörleri incelenip ve elde edilen sonuçlar, Log-Normal dağılım variyansınin, gölgeleme kontrolu için tek bir faktör olarak sayıldığını gösteriyor. Anahtar Kelimeler: Hiyerarşik Modülasyon, QAM Modülasyon, Çoklu Fading Channel, AWGN Kanal, Rayleigh Fading, Fading, Log-normal Gölgeleme Derinliği, Küçük Ölçekli Fading ve Büyük Ölçekli Fading
Master of Science in Electrical and Electronic Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Electrical and Electronic Engineering, 2013. Supervisor: Prof. Dr. Hasan Amca.
Keywords: Electrical and Electronic Engineering; Digital Communications; Hierarchical Modulation; Multipath Fading Channel; AWGN Channel; Rayleigh Fading; Depth of Shadowing; Log-normal Shadowing; Small Scale Fading and Large Scale Fading